Extracorporeal Shock Wave Therapy Promotes Osteogenic Differentiation in a Rabbit Osteoporosis Model - Li, Baofeng; Wang, Renkai; Huang, Xianyin; Ou, Yongliang; Jia, Zhenyu; Lin, Shanghui; Zhang, Ying; Xia, Hong; Chen, Bei (Frontiers in Endocrinology, 2021)
Extracorporeal shock wave therapy (ESWT) has been identified to accelerate bone formation. However, detailed mechanism has not been fully explained. In this study, we found that ESWT promoted osteoblast formation in vitro. Local ESW treatment of femur increased bone formation in vivo. Furthermore, changing the density or frequency of energy, there was no statistical difference in osteogenic differentiation. Therapeutically, local ESW therapy relieved bone loss and increased the number of bone trabecular in a rabbit osteoporosis model. Thus, ESWT may be a potential therapy by promoting osteoblast maturation.